Why are Hyperlinks to Business Websites Created? A Content Analysis - Vaughan, Liwen; Gao, Yijun; Kipp, Margaret E. I. (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l’ACSI, 2013)
Motivations for the creation of hyperlinks to business sites were analyzed through a content analysis approach. Most links were created for business purposes confirming findings from early quantitative studies that links contain useful business data. Links to competitors were extremely rare but competitors were often co-linked, suggesting that co-link analysis is the direction to pursue for information on competitive intelligence. Les motivations pour la création d’hyperliens pour les sites commerciaux ont été analysées à l’aide de l’approche de l’analyse de contenu. La plupart des liens ont été créés dans l’objectif d’une utilisation commerciale, confirmant les résultats obtenus des études quantitatives préliminaires suggérant que ces liens contiennent des données commerciales utiles. Les liens vers la concurrence étaient extrêmement rares, cependant les concurrents étaient souvent co-liés, suggérant que l’analyse des co-liens est la voie à poursuivre en ce qui concerne l’information en veille concurrentielle.